Effect of blueberry intervention on endothelial function: a systematic review and meta-analysis - Deng, B.; Lei, Y.; Zhou, R.; Ruan, T.; Lu, W.; Ying, J.; Yue, Y.; Mu, D. (Frontiers in Physiology, 2024)
Introduction Endothelial dysfunction indicates blood vessel injury and is a risk factor for cardiovascular diseases. Blueberry has been approved for its benefits on human health, especially on cardiovascular function. However, its effect on endothelial function remains unclear. We conducted a systematic review and meta-analysis to explore the impact of blueberries on endothelial function in adults.